2021
DOI: 10.22454/fammed.2021.355251
|View full text |Cite
|
Sign up to set email alerts
|

Gender Concordance of First and Senior Authors in Family Medicine Journals

Abstract: Background and Objectives: Women have increased in presence within academic family medicine over time yet remain underrepresented among senior faculty. Mentorship is a mechanism by which senior faculty support scholarly achievements, accelerating advancement of junior faculty. Methods: We analyzed 10 years (2008-2017) of original research articles in three peer-reviewed family medicine journals. We examined first author/last author pairs by gender as a proxy for mentorship of junior faculty by senior faculty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This was an unexpected result since typically the last author provides mentorship and has more experience and research expertise than the other authors. 7 For the JPAE articles reviewed in the current study, the PA first and last authors both demonstrated equal research experience and academic relevance, which may allude to more nuanced mentorship patterns among the listed PA authors than in classical medical literature; the PA last author might not necessarily serve as the team leader of the research project as would traditionally be expected. Some PA researchers might have had a more collaborative research system than traditionally anticipated.…”
Section: Discussionmentioning
confidence: 81%
“…This was an unexpected result since typically the last author provides mentorship and has more experience and research expertise than the other authors. 7 For the JPAE articles reviewed in the current study, the PA first and last authors both demonstrated equal research experience and academic relevance, which may allude to more nuanced mentorship patterns among the listed PA authors than in classical medical literature; the PA last author might not necessarily serve as the team leader of the research project as would traditionally be expected. Some PA researchers might have had a more collaborative research system than traditionally anticipated.…”
Section: Discussionmentioning
confidence: 81%
“…A study by Ghiasi et al ( 2015 ) showed that men dominate 80% of all the scientific production in Engineering, where there is a reproduction of the male-dominated scientific structures through repeating of predominantly male-driven collaborations. Some studies in Health Science, however, suggest that the increase in first and last authorship by women implies an improvement in gender advancement (Boekhout et al, 2021 ; Malchuk et al, 2021 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…. such as medicine (Malchuk et al, 2021). Authorship order is an important factor for hiring and promotion in some academic disciplines since the first authors are considered to play a leading role in the research and writing process and the last authors are commonly related to seniority (Walker et al, 2010;Helgesson and Eriksson, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authorship order is an important factor for hiring and promotion in some academic disciplines since the first authors are considered to play a leading role in the research and writing process and the last authors are commonly related to seniority (Walker et al, 2010;Helgesson and Eriksson, 2019). Female researchers are more likely to be first authors when the last author is also a woman rather than if it is a man (Aakhus et al, 2018;Malchuk et al, 2021). Women are also underrepresented in single-authored papers (West et al, 2013;Fox et al, 2018), which has high recognition in disciplines such as humanities (Helgesson and Eriksson, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation